Penerapan Supervisi Model 4s terhadap Pendokumentasian Asuhan Keperawatan Berbasis Emr di Rumah Sakit An-Nisa Tangerang - Meihati Munawaroh; Muhammad Hadi; Naryati Naryati; Tini Suminarti (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Nursing documentation is a series of documentation of activities carried out by the implementer, both manually and electronically, starting with assessment, making a diagnosis, action plan, implementation and evaluation, and must be the responsibility of the nurse. This study aims to determine the effectiveness of the 4S model supervision on EMR-based nursing care documentation. The method used in this study is the Generalized Linear Model Repeated Measure (GLM-RM) which is to analyze the effect of the 4S supervision model on EMR-based nursing care documentation in the control and intervention groups. From the results of the Generalized Linear Model Repeated Measure (GLM-RM), a comparison was obtained between the intervention group and the control group after the implementation of the 4S supervision model with a mean difference value = 33.56 with a p-value = 0.000. The results of the Generalized Linear Model Repeated Measure obtained the Greenhouse Geisser value obtained a significance value of 0.000, and the test of between-subjects effects showed that there was a difference in EMR-based nursing care documentation p-value 0.000 between the two groups. Based on the parameter estimates test, there was a difference in EMR-based nursing care documentation over time with a p-value = 0.000.The conclusion of this study is that there is an influence of the 4S supervision model on the documentation of EMR-based nursing care at An-Nisa Hospital, Tangerang. Keywords: Nursing Documentation, 4S Supervision.  ABSTRAK Dokumentasi keperawatan merupakan rangkaian pendokumentasian kegiatan yang dilakukan pelaksana, baik secara manual maupun elektronik, diawali pengkajian, membuat diagnosa, rencana tindakan, pelaksanaan dan evaluasi, dan harus menjadi tanggung jawab perawat. Penelitian ini bertujuan untuk mengetahui efektifitas supervise model 4S terhadap pendokumentasian asuhan keperawatan berbasis EMR. Metode yang digunakan dengan penelitian ini adalah Generalized Linear Model Repeated Measure (GLM-RM) yang dimana untuk menganalisa pengaruh model supervise 4S terhadap pendokumentasian asuhan keperawatan berbasis EMR pada kelompok kontrol dan intervensi. Dari hasil generalized Linear Model Repeated Measure (GLM-RM) didapatkan perbandingan pada kelompok intervensi dan kelompok kontrol  sesudah penerapan model supervise 4S denga nilai mean difference = 33,56 dengan p-value = 0,000. Hasil Generalized Linear Model Repeated Measure didapatkan nilai Greenhouse Geisser didapatkan nilai signifikansi 0,000, dan uji test of between-subjects effects didapatkan hasil bahwa terdapat perbedaan pendokumentsasuhan keperawatan berbasis EMR p-value 0,000 antara dua kelompok. Berdasarkan uji parameter estimates terdapat perbedaan pendokumentasian asuhan keperawatan berbasis EMR dari waktu ke waktu dengan nilai p-value = 0,000. Kesimpulannya dari penelitian ini adalah terdapat pengaruh model supervise 4S terhadap pendokumentasian asuhan keperawatan berbasis EMR di RS An-nisa Tangerang. Kata Kunci: Dokumentasi Keperawatan, Supervisi 4S.